El sentido de la muerte en Chile colonial - Retamal Ávila, Julio (Revista de Historia Social y de las Mentalidades, 2025)
This articlemakes an analytic contribution about t he different representations of death made by Chilean society during the colonian p eriod (16 th -17 th centuries). The author’s analysis is based on previous testaments g iven by men an women of that period that coexisted whit the uncertainty of life, planni ng their lives for the arrival of death. Throughout this legacy the author is able to descri be passages about the sense and importance of death and the practices and rites tha t it brings.